Інфографіка у комунікативному дизайні вебсайту - Селіванов, Іван Сергійович (Національний університет «Львівська політехніка», 2025)
The dissertation is devoted to the study of infographics, the substantiation of its theoretical and methodological foundations, and the analysis of the website as a communicative environment for information visualization. Based on the author's criteria, a multi-level structure of web-based infographics has been analyzed, and a project-evaluative model has been developed, which incorporates principles, methods, and assessment criteria, and has been tested within the educational process.
Infographics in communicative website design
Keywords: інфографіка, комунікативний дизайн, вебсайт, вебінфографіка, модель, інформація, теорія, дизайн методологія, комунікація, інтерактивність, дизайн, візуалізація, infographics, communicative design, website, web infographic, model, information, theory, design methodology, communication, interactivity, design, visualisation; 74:316:004.92](043.5)